Exercise Attenuates Brain Aging by Rescuing Down-Regulated Wnt/β-Catenin Signaling in Aged Rats - Chen, Dandan; Zhang, Ying; Zhang, Meng; Chang, Jingru; Zeng, Zhenzhong; Kou, Xianjuan; Chen, Ning (Frontiers in Aging Neuroscience, 2020)
Down-regulated Wnt signaling is involved in brain aging with declined cognitive capacity due to its modulation on neuronal function and synaptic plasticity. However, the molecular mechanisms are still unclear. In the present study, the naturally aged rat model was established by feeding rats from 6 months old to 21 months old. The cognitive capacity of aged rats was compared with young rats as the controls and the aged rats upon 12-week exercise interventions including treadmill running, resistance exercise, and alternating exercise with resistance exercise and treadmill running. Wnt signaling was examined in hippocampal tissues of the rats from different groups. Results indicated that the expression of Dickkopf-1 (DKK-1) as an antagonist of Wnt signal pathway, the activation of GSK-3β, and the hyperphosphorylated Tau were markedly increased as the extension of age. Meanwhile, higher p-β-cateninSer33, 37, Thr41 promoted neuronal degradation of aged rats. In contrast, three kinds of exercise interventions rescued the abnormal expression of DKK-1 and synaptophysin such as PSD-93 and PSD-95 in hippocampal tissues of the aged rats; especially 12-week treadmill running suppressed DKK-1 up-regulation, GSK-3β activation, β-catenin phosphorylation, and hyperphosphorylated Tau. In addition, the down-regulated PI3K/AKT and Wnt signal pathways were observed in aged rats, but could be reversed by resistance exercise and treadmill running. Moreover, the increased Bax and reduced Bcl-2 levels in hippocampal tissues of aged rats were also reversed upon treadmill running intervention. Taken together, down-regulated Wnt signaling suppressed PI3K/Akt signal pathway, aggravated synaptotoxicity, induced neuron apoptosis, and accelerated cognitive impairment of aged rats. However, exercise interventions, especially treadmill running, can attenuate their brain aging process via restoring Wnt signaling and corresponding targets.